Dimensi Autentik Multimodalitas Konteks Kultural dalam Pragmatik Edukasional - Permatasari, Agmi Sinta Nanda (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sriwijaya, 2024)
This study examines the authentic dimensions of multimodal cultural contexts in educational pragmatics and their significance in the context of learning and cultural understanding. The purpose of this research is to describe learning in the cultural context by using multimodality dimensions by using the research method of reading and note-taking techniques. The results and discussion in this study in visual communication conveyed in TikTok content found a cultural context that applies communication modes with visual, aural, linguistic, gestural and spatial aspects. Based on this, the authentic multimodal dimension of cultural context in educational pragmatics can significantly enrich learning and enhance understanding of culture in this era of globalization and multiculturalism.